1967
DOI: 10.1002/ar.1091590113
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of nerves in human primary teeth

Abstract: Human primary teeth in the stages of late root formation, mot completion and root resorption were impregnated with silver to allow study of the distribution of nerves in the pulp.Neural trunks composed of many individual, myelinated nerve fibers enter the apical foramen of primary teeth and pass in a coronal direction, often in close association with blood vessels. Neural trunks in the crowns of the teeth divide into smaller branches, which divide further into myelinated nerve fibers, which become interwoven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 7 publications
1
24
1
1
Order By: Relevance
“…ARPP21 is enriched in the caudate nucleus and cerebellar cortex, and regulates the effects of dopamine [74]. Although we were unable to determine the precise function of these genes, the up-regulation of genes related to neurological system processes in permanent PDL tissues is consistent with the degree of innervation being lower for deciduous incisors and canines than for permanent premolars [3], [75], [76].…”
Section: Discussionmentioning
confidence: 79%
“…ARPP21 is enriched in the caudate nucleus and cerebellar cortex, and regulates the effects of dopamine [74]. Although we were unable to determine the precise function of these genes, the up-regulation of genes related to neurological system processes in permanent PDL tissues is consistent with the degree of innervation being lower for deciduous incisors and canines than for permanent premolars [3], [75], [76].…”
Section: Discussionmentioning
confidence: 79%
“…However, historically, dentin hypersensitivity has been a useful term as it has described a distinct clinical entity familiar to the dental profession [13]. Some individuals also experience a vague dull, throbbing ache, persisting for variable periods of time after the stimulus has been removed [19]. Whilst this pain sensation could be part of the condition, it does not fit the definition, utilises C fibres in the innervation process and is highly likely to be due to pulpal inflammation, needing endodontic or exdontia management [10].…”
Section: Pain Mechanismsmentioning
confidence: 99%
“…One of the early, and most obvious hypotheses, was that dentin was innervated and therefore nerves were directly triggered by the stimulus. Histological stain techniques later proved not to be totally specific for nerve fibres [19]. Later evidence from electron microscopy revealed that nerve fibres do penetrate the dentinal tubules but only for a very short distance into the inner dentin, and mainly over the pulpal horns [20].…”
Section: Pain Mechanismsmentioning
confidence: 99%
“…For example, deciduous teeth exhibit less pain sensitivity when compared with permanent teeth as a result of differences in the number and/or innervation of their neural components, such as the Raschkow plexus [1], [2]. Deciduous teeth are composed of a less dense network of myelinated fibers than permanent teeth, and nerve fibers are seldom found in the calcified tissues of deciduous teeth [3], possibly related to why these teeth are less sensitive in pulp sensitivity tests. In addition, transient coronal discoloration and pulp canal obliteration after dental trauma are more frequent in deciduous teeth than in permanent teeth [4].…”
Section: Introductionmentioning
confidence: 99%